HLA-DRB1 and month of birth in multiple sclerosis. - Ramagopalan, S; Link, J; Byrnes, J; Dyment, D; Giovannoni, G; Hintzen, R; Sundqvist, E; Kockum, I; Smestad, C; Lie, B; Harbo, H; Padyukov, L; et al. (2009)
BACKGROUND: Multiple sclerosis (MS) displays a month-of-birth effect, with an excess of individuals being born in the spring and a deficit in the winter. This effect was shown to be more pronounced in familial cases of MS. In the present study, we investigated whether this month-of-birth association has any relation to the principal MS susceptibility gene, HLA-DRB1. METHODS: A total of 4,834 patients with MS, 4,056 controls, and 659 unaffected siblings from Canada, Sweden, and Norway were genotyped for the HLA-DRB1 gene. Month of birth was compared for patients, controls, and unaffected siblings with and without the MS risk allele HLA-DRB1*15. RESULTS: Significantly fewer patients with MS carrying the HLA-DRB1*15 risk allele were born in November compared with patients not carrying this allele (p = 0.02). Additionally, patients with MS carrying HLA-DRB1*15 had a higher number of April births compared with patients with MS not carrying HLA-DRB1*15 (p = 0.004). These differences were not present in controls or unaffected siblings. CONCLUSIONS: Month of birth, HLA-DRB1 genotype, and risk of multiple sclerosis are associated. The interaction of a seasonal risk factor with loci at or near HLA-DRB1 during gestation or shortly after birth is implicated.